Penerapan Metode Forward Chaining Untuk Rekomendasi Instalasi Local Area Network (LAN) - Pramana, Surya; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i02.P03, 2019)
Local Area Network (LAN) installation requires a special experience in selecting installation hardware and determining Internet Protocol (IP) addresses. However, cost of renting an IT network installer is very expensive, due that installation in medium and small scale companies is done by self-help, which is can be very detrimental. Based on that problem, the research was conducted with aim of helping medium and small scale companies to get recommendations for their company's LAN installations without hiring IT network installer by applying forward chaining method. This research produces 12 rules, which created based on parameters used, where recommendations are given based on conclusions that obtained from those rules. Usability testing is carried out using System Usability Scale (SUS) method and obtained result of 81. This indicates that method's usability is in an acceptable grade.